(untitled) (Journal of Science and Technology, 2016)
Spikelet sterility is the greatest barrier to rice hybridization. Two crosses IDSA 85/NERICA 1 and IDSA 85/JASMINE 85 were made to study the inheritance of spikelet fertility. Percent Spikelet fertility was obtained by calculating the number of filled spikelets as a percentage of the total number of spikelets. F2 spikelet fertility was then ranked into “low fertility class” plants and “normal fertility class” plants based on the fertility range of the less fertile parent. Any plant that fell into a fertility class similar to the range of fertility classes that the less fertile parent fell into was regarded as having a normal fertility and those that did not fall into this range were regarded as having a low fertility. There were significant differences (p<0.001) in mean fertility amongst the various populations in both crosses. Parents had significantly higher mean percent fertilities than F1 and F2 populations for both crosses. Mean percent fertility in F2 was significantly higher than F1 for the IDSA 85/NERICA 1 cross but there was no difference in F1 and F2 for the IDSA 85/JASMINE 85 cross. The F2 of the two crosses made in this study were found to have segregated into 9 low fertility plants: 7 normal fertility plants. This indicates that spikelet fertility in both crosses displayed duplicate recessive epistasis.